The association between screen use and child development: a literature review (Research, Society and Development, 2023)
Child development is essential for the formation of a more versatile and responsible citizen. Some factors can positively and negatively influence child development, based on the brain plasticity mechanism. Screen use enters as a negative factor and the objective of this study was to analyze how screen use is increasingly encouraged and exacerbated among children and how this practice can affect child development. In this study, a search was performed in the National Center for Biotechnology Information (PubMed) and Latin American and Caribbean Health Sciences (LILAS) databases, using the keywords: “screen time” and “child development”, where 1643 articles were found, and after the inclusion and exclusion criteria, 31 of them were used. The obtained results presented sleep disturbs, speech delay and psychological and behavioral symptoms as the most common unleashed problems by screen use. The data demonstrated that eletronic media use has been progressively encouraged and exacerbated among children, and that this practice is harmful for child development, especially on the scopes of sleep quality, speech development and psychological and behavioral well-being. Thus, it was analyzed that parents and caregivers should rethink their digital consume habits, and also must estimulate children through non-screen plays, in a way to minimize the injuries generated by excessive screen time.